The Relationship of Management Elements to The Waiting Time in Outpatient Registration of Soegiri Lamongan Hospital - Kafidhotin Azizah; Rafida Alifiyah Yusro; Tjatur Ermitajani Judi; Amirul Amalia; M. Ganda Saputra; Nihayatul Munaa; Lilis Maghfuroh (Jurnal Surya, 2024)
Introduction:     Time     Wait    Registration    Treat    Roads     at the hospital     Soegiri    Lamongan    known    from     30     they respond     The     observed    ,     show    that     19     they respond    or  63,3% tidak sesuai dengan standar (≤60 menit). This study aims to determine the relationship between management elements (Man, Method, Information and Time) and waiting time in outpatient registration of Soegiri Lamongan Hospital. Methods: This study used a cross sectional method, with an observational analytical design using an accidental sampling technique obtained from 100 respondents. The independent variable is the management element (Man, Method, Information and Time), and the dependent variable is the waiting time for outpatient registration. The instrument used management elements (Man, Method, Information and Time) using a closed questionnaire, waiting time using an open questionnaire. Results: The research found that the management elements of Man were 51% competent, Method 77% registered via Offline, Information 59% informative, Time 58% fast, and more than some patients stated that the waiting time was not suitable as many as 77 respondents (77%). This study uses the SPSS 25 For Windows program using the Chi Square test with a value of α=0.05 obtained a value of Man p = 0.000, Method p = 0.001, Information p = 0.000, Time p = 0.006 meaning that there is a relationship between management elements (Man, Method, Information and Time) to the waiting time in the outpatient registration of Soegiri Lamongan Hospital. Conclusion: It is hoped that the outpatient unit will further increase the speed of waiting time in outpatient registration through improving the competence of registration officers by taking courses, participating in various trainings, and taking competency certification tests. Keywords: Health worker, Knowledge, Occupational Health and Safety (K3)